Status of Height in Children Aged 4 to 14 Years in Relation to Mid Parental Height- An Observational Study (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: The adult height of a growing child largely depends on the heredity. The present height status of a child can be determined by mid parental height. This study is an initial step to determine the status of height in children between 4 years to 14 years in relation to mid parental height.Objective: To assess the status of height in relation to parental height in children aged between 4 to 14 years and to assess other factors (birth order, number of younger siblings, gestational age at birth, birth weight, feeding in first six month of age, maternal age at child birth, maternal education, crowding, monthly family income and area of residence) that may influence height, other than parental height.Materials and Methods: A cross-sectional observational study was conducted on 100 children of age between 4 years to 14 years attending outpatient department and inpatient department of Sher-E-Bangla Medical College Hospital, Barisal from 1st March 2011 to 31st August 2011. Data were collected through interviewing with pre-designed questionnaire and anthropometry.Results: A total 100 children of 4 to 14 years of age were enrolled during the study period. Among them 46 were male and 54 were female. Among all the cases under study, 60 cases were appropriate in status of their height in relation to their parental height, whereas 20 cases were tall in status and another 20 cases were short in status in relation to their mid-parental height. Apparently, it seems both the tall and short cases were equal in number, but the mean of Z scores of all children under the study was -0.432 and median was -0.55 which indicates the overall loss of height. Higher maternal age, appropriate gestational age, higher birth weight, first birth order and higher maternal educational status came out to be having strong influence on higher height in relation to mid parental height while higher total family income had weaker influence.Conclusion: Height status of our country is almost static in condition, but there is slight inclination towards being shorter in future. Though very apparent but male children are in slight shorter while female children are apparently taller in status, which may be due to early age of puberty in case of female children.Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 72-78